Arsenicos is: A Review of Its Diagnosis and Treatment (Medicine Today, 2018)
Prolong ingestion of arsenic contaminated water affects human health severely. More than 67 million people in Bangladesh are exposed to 0.05 mg/ liter or above of arsenic in their drinking water and it is now considering a biggest crisis in health and social sector in the modern world. Arsenicosis affects almost all the vital system of the body. Skin involvement is the earliest and commonest feature. Diagnosis is usually done by history, clinical feature and laboratory analysis. Still there is no international consensus on its diagnosis and treatment. Antioxidant and food supplements are tried with different range of success. In this article, author describes the extent of arsenicosis and elaborates its diagnosis and treatment.Medicine Today 2018 Vol.30(2): 81-88